The readiness of Malaysia medium - sized enterprises in manufacturing sector to adopt information communication technology - Ng, Boon Beng (2007)
The Government of Malaysia invested extensively to induce SMEs in the manufacturing sector to adopt ICT usage. It has encouraged them to collaborate and forge linkages with larger companies through ICT usage. Despite the Government’s efforts and resources, these SMEs were not perturbed to adopt new systems. The low level of ICT adoption reported by SMIDEC posed two vital questions. (1) Do SMEs see the need to adopt ICT and are they ready to use them? (2) Do SMEs know that ICT could help them enhance their business competitiveness? None of the research done locally or overseas have taken a holistic approach to identify issues, motivators and the Stages of ICT Adoption. The objective of this research is to provide an analytical insight on SMEs, using medium-sized enterprises (MSEs) in the manufacturing sector as the research target. A quantitative survey was conducted to collate empirical data via surface mail, fax, and telephone follow-up. Out of the 1975 target respondents only 295 MSEs were qualified for this survey. Three sets of core information were derived from data analysis i.e. Barriers, Facilitators and Stages of ICT Adoption. The derived statistical evidences have proven the validity of hypotheses and the usability of ICT Adoption Identification Model (I-AIM), as they explain the MSEs predicament in ICT adoption. The MSEs ICT adoption issues were comprehensively explored, discussed and considered even from the technology suppliers’ perspective. This holistic approach allows MSEs to see the value proposition and positive differentiation through the adoption of ICT. It is pragmatic to find the right business catalysts prior to venturing into ICT adoption. The proposed model has vividly illustrated a linear relationship among Barriers, Facilitators and Stages of ICT adoption. In summary, the MSEs are convinced of the ICT usefulness but they still need to be persuaded to adopt it. It is confirmed by this research that only 65% of MSEs have adopted ICT and only 5.4% of which are at Stage Four of the ICT Adoption. SMIDEC and WITSA have also reported similar findings.